Installation of a getter vacuum pump in cathode-anode region of a high-power klystron amplifier - Propose and feasible - Degasperi, F. T.; Verardi, S. L L; Motta, C. C. (Institute of Electrical and Electronics Engineers (IEEE), 2006)
The possibility to install a getter vacuum pump and its feasible in the anode of a high-power klystron amplifier is investigated in order to decrease of the pressure in the gun and consequently increasing its lifetime. The study is conducted using a 1.3 GHz, 100 A and 240 kV high-power klystron with five reentrant coaxial cavities, assembled in a cylindrical drift tube 1.2 m long. This work takes into account the specific conductance of components of gun and all important gas sources, like the degassing of the drift tube, the cavity walls, the cathode, the anode, and the collector, as well the position and pumping speed of the getter vacuum pump in anode region. © 2006 IEEE.
Keywords: Getter; High-vacuum modeling; Ultra high-vacuum system; Vacuum pressure field; Amplifiers (electronic); Anodes; Cathodes; Electron tubes; Getters; Klystrons; High vacuum modeling; Ultra high vacuum system; Vacuum pumps